Identification of POLR3B biallelic mutations‐associated hypomyelinating leukodystrophy‐8 in two siblings. Issue 5 (21st January 2023) - Yang, Fan; Sun, Huaqin; Yang, Yanting; Wang, Yanan; Dai, Siyu; Lin, Ziyuan; Shen, Ying; Liu, Hongqian
Abstract: POLR3B gene encodes the 2nd largest catalytic subunit and affects the function of RNA polymerase III enzymes in transcription. Bi‐allelic variants in POLR3B pathogenically cause hypomyelinating leukodystrophy‐8 (HLD8). Herein, we recruited a family with two patients, who presented clinically with cerebellar atrophy, intellectual disability, hypogonadotropic hypogonadism, and visual problems. We identified the two affected siblings carrying the compound heterozygous variations (c.165_167del; c.1615G>T) in POLR3B by trio‐whole‐exome sequencing (trio‐WES). The qPCR and western blot showed that both transcriptional and translational levels of the mutation (c.165_167del, p.I55_K56delinsM) were sharply attenuated. Following that, a thorough functional examination of a zebrafish line disrupted for human POLR3B validated the pathogenic effects of the two mutations. Our research broadens the spectrum of HLD8‐related pathogenic POLR3B mutations and provides new molecular and animal evidence. Abstract : In our study, we identified the two affected siblings who carried the variations (c.165_167del; c.1615G>T) in POLR3B by trios‐WES. Combining silico analysis, transcription and translation analysis, and verification in the zebrafish model, we provide evidence of the pathogenic effect of the biallelic mutations.